KONTRIBUSI UNI EROPA DALAM IMPLEMENTASI JORDAN COMPACT UNTUK MEMBANTU PENGUNGSI SURIAH DI YORDANIA (2016-2021) - Rahayu, Mutiara Rizky; Takwa, Tuah Kalti (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2026)
This study examines the European Union’s contribution to the implementation of the Jordan Compact (2016–2021) as a response to the Syrian refugee crisis in Jordan. Using a qualitative case study approach based on official EU documents, international reports, and academic literature, the study finds that the EU played a central role through three dimensions: financial support, trade and labor policy measures, and institutional coordination. The Jordan Compact contributed to increasing formal work permits for Syrian refugees and strengthening Jordan’s fiscal stability. However, its impact on long-term economic transformation, job quality, gender inclusion, and reduced aid dependency remains limited. The findings also indicate that the EU’s contribution is shaped by broader strategic interests, particularly regional stabilization and external migration management. Therefore, while significant, the EU’s role cannot be considered fully transformational. Keywords: European Union, Jordan Compact, migration.